Neo-Victorian Hidden Object Games, Participatory Culture, and the Interaction Between Past and Present. (29th April 2017) - Ioannidou, Elisavet
Abstract: This essay examines the adaptation of Victorian literary works into neo-Victorian hidden object games, in order to demonstrate how characteristics such as interaction, immersion, and the simulation of sensory perception inform neo-Victorianism's return to and engagement with the past. Emerging, by means of their medium-specific attributes, as examples of participatory culture, neo-Victorian hidden object games problematize traditional notions about the clear-cut roles of producers and consumers, highlighting neo-Victorianism's involvement in the process of adaptation, and complicating the genre's understanding of the dynamic between past and present; though making a case both for the present's capability as opposed to the past's helplessness, and for the present's procedural role in manifesting the past's authority, the complex structures of interaction between the Victorian gameworld and the twenty-first-century player ultimately establish the relationship between past and present as one of collaboration.